Doppler weather radars as a game changer in desert locust swarm tracking - N. A. Anjita; J. Indu; P. Thiruvengadam; Vishal Dixit; Arpita Rastogi; Bagavath Singh Arul Malar Kannan (Scientific Reports)
Abstract Desert locusts, notorious for their ruinous impact on agriculture, threaten over 20% of Earth’s landmass, prompting billions in losses and global food scarcity concerns. With billions of these locusts invading agrarian lands, this is no longer a thing of the past. Recent invasions, such as those in India, where losses reached US$ 3 billion in 2019-20 alone, underscore the urgency of action. By tapping into the existing Doppler Weather Radar (DWR) infrastructure, originally deployed for meteorological applications, the present study demonstrates a systematic approach to distinctly identify and track concentrations of desert locust swarms in near real-time using single and dual-polarization radars. Findings reveal the potential to establish early warning systems with lead times of 5–7 h and spatial coverage of approximately 100 km, empowering timely mitigation efforts. In stark contrast to satellite imagery, often constrained by resolution limitations that impede swarm detection, DWRs offer unparalleled spatial and temporal resolution, rendering them indispensable tools in this endeavour. Harnessing radar capabilities within the current infrastructure, unleashes unparalleled ecological monitoring potential and fundamentally transform practices in managing migratory pest management practices. Embracing these technological advancements becomes imperative to safeguard agricultural landscapes, uphold global food security, and effectively mitigate the ecological threats posed by migratory pests.